A sociolinguistics of diaspora : Latino practices, identities, and ideologies (Routledge Critical Studies in Multilingualism, 2015)
"This volume brings together scholars in sociolinguistics and the sociology of new media and mobile technologies who are working on different social and communicative aspects of the Latino diaspora. There is new interest in the ways in which migrants negotiate and renegotiate identities through their continued interactions with their own culture back home, in the host country, in similar diaspora elsewhere, and with the various "new" cultures of the receiving country. This collection focuses on two broad political and social contexts: the established Latino communities in urban settings in North America and newer Latin American communities in Europe and the Middle East. It explores the role of migration/diaspora in transforming linguistic practices, ideologies, and identities"--